IMPROVING THE STUDENTS' ABILITY IN READING COMPREHENSION THROUGH DISCOVERY LEARNING METHOD AT THE EIGHT GRADE OF SMP NEGERI 1 GIDO - GULO, LESTA APRILDA; MARU'AO, NURSAYANI; DAELI, HIDAYATI; TELAUMBANUA, YASMINAR AMAERITA (CENDEKIA: Jurnal Ilmu Pengetahuan, 2024)
Reading comprehension is the process and activity of understanding all reading texts that include vocabulary and concepts, making conclusions, and connecting key ideas, in addition, readers will get ideas or meanings from written texts. One of the problems found by researchers is that students can’t understand the whole of each word. The purpose of this study is to improve students' reading comprehension using the Discovery Learning method in the eighth grade of SMP Negeri 1 Gido in the 2022/2023 academic year. Researchers use Classroom Action Research (CAR), especially Quantitative Methods as a research method. There are two cycles, each cycle consists of two meetings. Each meeting consist of planning, action, observation and reflection. Data were collected by researchers from observation results, field notes and evaluation papers. From the results of the study in each cycle, it has been shown that students have improved by using the Discovery Learning Method. In Cycle I students failed, the average student score was 46.8. In Cycle II all students successfully passed the Minimum Competency Criteria. The average students score was 88.6. The researchers concluded that the best way to improve students' Reading comprehension is to use the Discovery Learning Method. Therefore, the researchers has several recommendations such as the researchers recommends students and teachers to use the Discovery Learning method to improve their reading comprehension, finally the researchers recommends all readers especially to the next researchers to explore Reading comprehension that has not been explored by the researchers in this study. ABSTRAKPemahaman membaca adalah proses dan aktivitas untuk memahami semua teks bacaan yang mencakup kosa kata dan konsep, membuat kesimpulan, dan menghubungkan ide-ide kunci, di samping itu pembaca akan mendapatkan ide atau makna dari teks tertulis. Salah satu masalah yang ditemukan peneliti adalah siswa tidak dapat memahami keseluruhan setiap kata. Tujuan penelitian ini adalah untuk memperbaiki pemahaman membaca siswa dengan menggunakan metode Discovery Learning di kelas VIII SMP Negeri 1 Gido tahun 2022/2023. Peneliti menggunakan Penelitian Tindakan Kelas (PTK) khususnya metode kuantitatif sebagai metode penelitian. Ada dua siklus yang siklusnya terdiri dari dua pertemuan. Setiap pertemuan terdiri dari perencanaan, tindakan, observasi dan refleksi. Data dikumpulkan oleh peneliti dari hasil observasi, catatan lapangan dan lembar evaluasi. Dari hasil penelitian di setiap siklus, telah ditunjukkan bahwa siswa mendapatkan peningkatan dengan menggunakan Metode Discovery Learning. Pada Siklus I siswa gagal, nilai rata-rata siswa adalah 46, 8. Pada Siklus II semua siswa berhasil melewati Kriteria Kompetensi Minimal. Nilai rata-rata siswa adalah 88,6. Para peneliti menyimpulkan cara terbaik untuk memperbaiki pemahaman membaca siswa adalah menggunakan Metode Discovery Learning. Oleh karena itu, peneliti memiliki beberapa rekomendasi seperti peneliti merekomendasikan siswa dan guru menggunakan metode Discovery Learning untuk memperbaiki pemahaman membaca mereka, akhirnya peneliti merekomendasikan semua pembaca terutama kepada peneliti berikutnya untuk mengeksplorasi pemahaman membaca yang belum dieksplorasi oleh peneliti dalam penelitian ini.